Pre-Service English Teachers’ Perception about Language, Culture, Identity and Difference in Language Learning - Antonia Tefa; Konradus Silvester Jenahut (Leksikon: Jurnal Pendidikan Bahasa, Sastra, dan Budaya, 2023)
In foreign language learning, and teaching, the concepts of language, culture, identity and difference, and their relationship are contentious topics. What is culture? What is identity? What is difference? What connection do they have to language? What part should the culture of the learners have in learning about the culture of the target? Questionnaires and Focus group discussion were used to collect the data. This study explores pre-service English teachers’ in a private university in East Nusa Tenggara perceptions about language and culture in language learning. The results show how pre-service English teachers’ perceptions of language and culture fit into a humanistic and functional framework in relation to language learning. Participants also mentioned the value of language acquisition in understanding cultural diversity and cultural identity.